A method for transportation mode choice - Gursoy, Mustafa (ACADEMIC JOURNALS, 2010)
This paper deals with the problem of choosing the best possible shipping alternative among a set of transportation modes (under) with four considered decision criteria. An AHP-like model used to solve the problem. The developed model was run with rail-road-sea transportation combination for Turkey. The model is applied to rail-road-sea transportation combination in Turkey. Instead of considering different commodity types just textile sector modeled and studied for simplicity. It is shown that the proposed model is very flexible (depending on) with (the) considered criteria. A short poll was conducted to find out the most important decision criterion of shippers. Then the first four most preferred criteria of respondents chosen for embodying into the model. At the end the model validity has proven by almost eighty percent of accuracy along with the real life choices of the shippers.
Keywords: Multimodal transportation; logistics; freight transportation; transportation planning; NETWORK; INVENTORY; COSTS; Science & Technology - Other Topics